Coaching jako proces wspierający racjonalne działanie organizacji = Coaching as a support process of rational action of the organization - Czardybon, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is devoted to coaching - one of the new and dynamic developing methods supporting the functioning of the organization. Coaching is an opportunity to enhance the overall efficiency and effectiveness of the organization's activities. During the subsequent coaching sessions are considered concrete proposals for solutions; the identified needs are trying to choose the appropriate measures. Contributing to the development of individual employees, coaching at the same time supports the development of the entire organization. The process of coaching can strengthen the organization through the development of appropriate attitudes. Also in the long term it is the process of accelerating the development of the organization.
Keywords: coaching; organizacja; racjonalne działanie; zmiana; rozwój; organization; rational action; change; development